Biomaterials Used for Suture Anchors in Orthopedic Surgery - Cho, Chul-Hyun; Bae, Ki-Cheor; Kim, Du-Han (Clinics in orthopedic surgery, 2021)
Suture anchors are broadly used for attaching soft tissue (e.g., tendons, ligaments, and meniscus) to the bone and have become essential devices in sports medicine and during arthroscopic surgery. As the usage of suture anchors has increased, various material-specific advantages and challenges have been reported. As a result, suture anchors are continually changing to become safer and more efficient. In this ever-changing environment, it is clinically essential for the surgeon to understand the key characteristics of existing anchors sufficiently. This paper aims to summarize the current concepts on the characteristics of available suture anchors.